DAMPAK FANATISME PENGGEMAR IDOL GRUP KOREA TERHADAP GAYA HIDUP REMAJA DALAM PERSPEKTIF ISLAM - Afzan, Rifyal Fariz (ANDRAGOGI, 2022)
Fanaticism can be influenced by a desire to be a fan for something in the form of people or goods, and can change the individual's behavior in doing new things. The existence of this fanaticism can have a positive or negative impact. The purpose of writing this article is to find out how Islam responds to the impact of fanaticism of Korean idol group fans on adolescent lifestyles from an Islamic perspective. This research used descriptive qualitative. The data used were obtained through questionnaires that were disseminated through social media and literature studies on several articles related to the research and then analyzed and reviewed so as to obtain conclusions. The results of the study are that the fanaticism of Korean idol group fans can have a negative impact on teenagers' lifestyles, one of which is consumptive nature and the teenagers appearance. In an Islamic perspective, this is certainly not recommended, because in Islam itself there are rules on how to use all things that are beneficial to oneself or others in moderation as well as rules for how to dress in accordance with Islamic law. In Islam itself is also recommended to use the time to do activities that are more useful.Â